Latent tuberculosis infection in rural China: baseline results of a population-based, multicentre, prospective cohort study. Issue 3 (March 2015) - Gao, Lei; Lu, Wei; Bai, Liqiong; Wang, Xinhua; Xu, Jinsheng; Catanzaro, Antonino; Cárdenas, Vicky; Li, Xiangwei; Yang, Yu; Du, Jiang; Sui, Hongtao; Xia, Yinyin; et al.
Summary: Background: Prophylactic treatment of individuals with latent Mycobacterium tuberculosis infection is an essential component of tuberculosis control in some settings. In China, the prevalence of latent tuberculosis infection, and preventive interventions against this disease, have not been systematically studied. We aimed to assess the prevalence of latent tuberculosis and its associated risk factors in rural populations in China. Methods: Between July 1, and Sept 30, 2013, we undertook a baseline survey of a population-based, multicentre, prospective cohort study of registered residents (≥5 years old) at four study sites in rural China. Eligible participants were identified by door-to-door survey with a household sampling design. We screened participants for active tuberculosis and history of tuberculosis then used a tuberculin skin test and an interferon-γ release assay (QuantiFERON [QFT]) to test for latent infection. We used odds ratios (ORs) and 95% CIs to assess variables associated with positivity of QFT and tuberculin skin tests. Findings: 21 022 (90%) of 23 483 eligible participants completed a baseline survey. Age-standardised and sex-standardised rates of skin-test positivity (≥10 mm) ranged from 15% to 42%, and QFT positivity rates ranged from 13% to 20%. Rates of positivity for the tuberculin skin test and the QFT test were low in study participants younger than 20 years and gradually increased with age (p for trend <0·0001). Rates of latent tuberculosis infection were higher for men than women (p<0·0001). Overall agreement between the tuberculin skin test and the QFT test was moderate (81·06%; kappa coefficient 0·485), with skin-test-only positive results associated with the presence of BCG scar, male sex, and ages of 60 years and older, and QFT-only positive results associated with male sex and ages of 60 years and older. Interpretation: On the basis of findings showing that the performance of the tuberculin skin test might be affected by various factors including BCG vaccination and age, our results suggest that the prevalence of latent tuberculosis in China might be overestimated by skin tests compared with interferon-γ release assays. Funding: The National Science and Technology Major Project of China, the Program for Changjiang Scholars and Innovative Research Team in University of China.